2016
DOI: 10.3390/app6120432
|View full text |Cite
|
Sign up to set email alerts
|

A Label-Free Aptamer-Based Fluorescent Assay for Cadmium Detection

Abstract: Selective detection of ultratrace amounts of cadmium (Cd 2+ ) is extremely important for food safety and environmental monitoring because of its toxicity and widespread use. In this work, we developed a facile, rapid, sensitive, and highly selective method for the detection of Cd 2+ based on a label-free aptasensor using an unmodified double-stranded deoxyribonucleic acid-specific dye (PicoGreen). The linear range was 0.10-100 µg/mL, and the detection limit (0.038 ng/mL) was lower than the guideline from the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…These interactions include protein-protein, protein-antibody, protein-aptamer, DNA-DNA, DNA-RNA, probe-receptor, probe-glycan, and probe-lipid. With these wide range options, panels of biosensors were generated [11,[36][37][38][39]. However, the preferences fall with the affinity between the desired target molecule/biomarker of interest against the probe, which can capture the targeted molecule.…”
Section: Resultsmentioning
confidence: 99%
“…These interactions include protein-protein, protein-antibody, protein-aptamer, DNA-DNA, DNA-RNA, probe-receptor, probe-glycan, and probe-lipid. With these wide range options, panels of biosensors were generated [11,[36][37][38][39]. However, the preferences fall with the affinity between the desired target molecule/biomarker of interest against the probe, which can capture the targeted molecule.…”
Section: Resultsmentioning
confidence: 99%
“…A label-free aptasensor approach for Cd (II) detection was independently exploited by Y. Luan et al [72] and B. Zhou et al [73], combining an aptamer with unmodified dsDNA-specific dye. Based on the principle that hybridization of two aptamers boosts the fluorescence engendered during the reaction, B. Zhou et al showed that, in the absence of Cd 2+ , SYBR green-I binds to the small groove of dsDNA (aptamer-complementary strand) establishing the dsDNA–dye complex and generating high fluorescence signal.…”
Section: Biosensing Methodsmentioning
confidence: 99%
“…After the introduction of complementary strands and Pico Green dye (PG), a hybrid with the residual free aptamers that did not bind with Cd 2+ is formed. This results in a higher PL signal (Figure 4e), allowing a higher sensitivity (LOD of 0.038 ng/mL) [72].…”
Section: Biosensing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, two different aptamers of Cd 2+ have been respectively selected by two independent groups [26,27]. Then, colorimetric [28] and fluorescent methods [26,29] were exploited to determine Cd 2+ . As for electrochemical methods, they are sensitive, and some portable devices are already commercial and available, including pocketSTAT2 (Ivium Technologies, Netherlands), PalmSens4 (Palmsens, Netherlands), μStat-i 400 (Metrohm, Switzerland) and CHI1200C (CH Instruments, China).…”
Section: Introductionmentioning
confidence: 99%